Maqhasid Sharia: Measurement of the Purpose of Islamic Banks in Indonesia with Sharia Compliance as a Moderating Variable - Azmi, Fika; Pramono, Nugroho Heri; Wahyuni, Mirasanti (Universitas Negeri Semarang, 2020)
The purpose of this study is to analyze the effect of Islamic social reporting index which is moderated by sharia compliance on maqhasid sharia index. The population of this study was 14 Islamic banks in Indonesia. Meanwhile, the sample used was the annual report of Islamic banks from 2014-2018 a total of 70 observational data. The sampling technique used was simple random sampling. The data analysis method used was regression with moderation. Based on the results of the partial test, Islamic social reporting index and sharia compliance individually affect the maqhasid sharia index. In addition, based on the results of the regression test with moderation, the Islamic social reporting index moderated by sharia compliance affects on the maqhasid sharia index. Thus, the conclusion is that sharia compliance is proven to moderate the effect of Islamic social reporting index on the value of the maqhasid sharia index. A negative coefficient value indicates that the effect given is negative. The point is that the increase in the number of sharia complications has the effect of reducing or weakening the effect of the Islamic social reporting index on the value of the maqhasid sharia index.